2014
DOI: 10.9790/2402-08426875
|View full text |Cite
|
Sign up to set email alerts
|

Community Participation in Wildlife Conservation in Amboseli Ecosystem, Kenya

Abstract: Amboseli National Park is regarded as one of the most economically significant parks owing to high tourist visitation and revenue streams. Despite the economic significance of Amboseli National Park, the wildlife dispersal areas outside the park boundaries are shrinking at an alarming rate due to changing land use activities and a growing human population pressure, aggravating human -wildlife conflicts as well as creating unviable ecosystem for wildlife. The park cannot support the current wildlife populations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 3 publications
0
10
0
Order By: Relevance
“…In addition, there are weaknesses in the management system of wetland resources. In particular, the legal system is inconsistent, overlapping in the functions of the management agencies, property rights are not clearly demarcated, financial sources for conservation are less sustainable, lack databases and scientific information for management ( Kipkeu et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, there are weaknesses in the management system of wetland resources. In particular, the legal system is inconsistent, overlapping in the functions of the management agencies, property rights are not clearly demarcated, financial sources for conservation are less sustainable, lack databases and scientific information for management ( Kipkeu et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…1) located on the Kenyan-Tanzania border, covering the 388 km 2 Amboseli National Park and surrounding Maasai group ranches (Western et al 2015). The national park, covering 7% of the ecosystem, serves as a dry season concentration area for livestock and wildlife due to the series of swamps within (Kipkeu et al 2014). The area experiences bimodal rainfall with peaks from March to May and October to December (Campbell et al 2005), and drought is a common feature in the area.…”
Section: Study Areamentioning
confidence: 99%
“…In Kenya, for example, most of the national parks and reserves are heavily dependent on surrounding community and private owned lands for their ecological survival and integrity [38]. Research has shown that information on perception and attitudes of local communities living in and around protected areas is important to identify management programs and strategies that best suit the protection of biodiversity alongside the development of local community livelihoods [39][40][41][42][43]. This study explores not only local Lambwe Community attitudes but also their level of awareness of wildlife snaring in the region.…”
Section: Introductionmentioning
confidence: 99%